A Study of Consumer Preferences towards Green Consumer Durables: An Empirical Approach - Sangeeta , Ms.; Kanwa , Dr. Anil (American Journal of Economics and Business Management, 2023)
The objective of the present study is to examine the consumer preference regarding green durables. To achieve the objective primary data has been collected from green consumers of Haryana State, India only. The total 500 respondents were interviewed so total sample for the study is 500. The self-structured questionnaire has been used to assess the consumers’ preference on five point Likert scale. Simple random sampling method has been used to collect the data. Findings the study suggested that majority of consumers were not prefer green air conditioner, microwave, washing, refrigerator and laptop as a green durable. The study also found that female respondents’ preference is high for green microwave, washing, refrigerator and laptop than the males. Further, it is concluded that unmarried respondents’ preference is high for green air conditioner, microwave, washing, refrigerator and laptop than the males.